1996
DOI: 10.1055/s-2007-972861
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blood Lactate Concentrations Obtained During Incremental and Constant Intensity Exercise

Abstract: Differences in blood lactate concentrations obtained during step-wise incremental and constant running exercise at the same intensities were investigated. In addition, the effect of endurance running at a constant intensity obtained by three different incremental modes (OBLA-4, 6 or 8 min) on the blood lactate concentration were studied. Eight firemen and six marathon runners performed: 1) three step-wise incremental running (IR) treadmill tests, each consisting of either 5 x 4, 5 x 6 or 5 x 8 min, and, 2) six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
9

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 4 publications
5
37
0
9
Order By: Relevance
“…Collectively, the present studies provide a significant contribution to a limited body of recommendation for accurately determining LT2 is consistent with others [16,283,284] , and supported by the results of this thesis that show LT2 elicited a V O2, heart rate, [La -] and (albeit inconsistently) power output that was similar 279 to those elicited during 40 km cycling time trials. Thus, its validity for establishing a performance intensity was confirmed.…”
Section: Practical Implicationssupporting
confidence: 89%
See 1 more Smart Citation
“…Collectively, the present studies provide a significant contribution to a limited body of recommendation for accurately determining LT2 is consistent with others [16,283,284] , and supported by the results of this thesis that show LT2 elicited a V O2, heart rate, [La -] and (albeit inconsistently) power output that was similar 279 to those elicited during 40 km cycling time trials. Thus, its validity for establishing a performance intensity was confirmed.…”
Section: Practical Implicationssupporting
confidence: 89%
“…The study of Bishop et al [10] reported stage durations of 3 min, 162 however it has been concluded that stages shorter than 5 min may over-predict LT2. and therefore an accurate determination of LT2 [282][283][284] . The study of Fell [18] reported a larger variation in LT2 power output (260 ± 42 W) than the present study (238 ± 28 W), and larger variation is known to result in stronger relationships with endurance performance [1] .…”
Section: Correlations With 40 Km Time Trial Performancementioning
confidence: 99%
“…Níveis elevados de lactato no sangue são evidentes após o exercício de resistência de alta intensidade 8 . O lactato do sangue normalmente retorna aos níveis de repouso aproximadamente uma hora após o término do exercício 8 . A força tem-se mostrado reduzida até quatro horas após o término do exercício de resistência 2 .…”
Section: Discussionunclassified
“…Alguns protocolos manipulam a duração de cada estágio incremental, a inclinação ou os intervalos entre cada estágio incremental. Na literatura verificam-se estudos que compararam protocolos com diferentes durações dos está-gios de corrida incremental 5,10 , e protocolos com incrementos distintos -velocidade e inclinação da esteira 11 . No entanto, faz-se necessária a realização de estudos que comparem os efeitos de diferentes intervalos entre os estágios de velocidade de protocolos incrementais de corrida na determinação de limiares.…”
Section: Introductionunclassified